The Role Of Constitutional Law in Regional Autonomy - Deltanto Sarwi Diatmiko, Raden; Djunaedi, O.; Akkapin, Supaphorn (CV. Era Digital Nusantara, 2024)
This research aims to analyse the influence of constitutional law foundations on the implementation of regional autonomy policies in Indonesia. Using a normative legal research methodology with a statutory approach, this study examines the legal norms governing regional autonomy as well as analyses the authority between the central and regional governments. The results show that the clarity of legal regulations contributes significantly to the effectiveness of regional autonomy, while overlapping authority and weak monitoring mechanisms are obstacles. This study concludes that strengthening regulations and public participation are essential to improve the successful implementation of regional autonomy policies.